Approaches to World Literature - Küpper, Joachim (WeltLiteraturen / World Literatures, 2013)
The present volume introduces new considerations on the topic of World Literature, penned by leading representatives of the discipline from the United States, India, Japan, the Middle East, England, France and Germany. The essays revolve around the question of what, specifically in today's rapidly globalizing world, may be the productive implications of the concept of World Literature, which was first developed in the 18th century and then elaborated on by Goethe. The discussions include problems such as different script systems with varying literary functions, as well as questions addressing the relationship between ethnic self-description and cultural belonging. The contributions result from a conference that took place at the Dahlem Humanities Center, Freie Universität Berlin, in 2012.